Potentialities of polyhydroxyalkanoate (PHA) producing bacteria isolated from Asparagus officinalis L. - Altamirano, Luz (2020)
Objective: to determine the production of polyhydroxyalkanoates produced by potentially nitrogen-fixing bacteria isolated from Asparagus officinalis L. Methods: Samples of rhizospheric soil, previously disinfected roots and stems, were cultivated in nitrogen-free media to isolate rhizospheric and endophytic fixing bacteria, respectively. In a fermentation broth with glycerol as a carbon source, the production of PHA granules by these bacteria was investigated, staining them with Sudan Black B after 24 and 48 hours. The two bacterial cultures in which the highest number of cells with PHA granules were observed were fermented with glycerol in the balanced and unbalanced media for 36 hours, determining the biomass. Result: 51.1% of the fixing bacteria were rhizospheric and 48.9% endophytic. PHA granules were detected in 56.67% of the bacteria. Yp / x yield was 0.57855 g / g (Azospirillum sp.155) and 0.22543 g / g (Azospirillum sp.130) in the balanced medium and 0.76718 g / g (Azospirillum sp.155) and 0.26229 g / g (Azospirillum sp. 130) in the unbalanced medium, after 32 hours of fermentation. Conclusion: PHA production by nitrogen-fixing bacteria isolated from asparagus was demonstrated.